(untitled) (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: Anaphylaxis is a medical emergency and requires prompt treatment to prevent life-threatening conditions. Epinephrine, considered as the first-line drug, is often not administered. We aimed first to analyse the use of epinephrine in patients with anaphylaxis in the emergency department of a university hospital and secondly to identify factors that influence the use of epinephrine. METHODS: We performed a retrospective analysis of all patients admitted with moderate or severe anaphylaxis to the emergency department between 1 January 2013 and 31 December 2018. Patient characteristics and treatment information were extracted from the electronic medical database of the emergency department. RESULTS: A total of 531 (0.2%) patients with moderate or severe anaphylaxis out of 260,485 patients admitted to the emergency department were included. Epinephrine was administered in 252 patients (47.3%). In a multivariate logistic regression, cardiovascular (Odds Ratio [OR] = 2.94, CI 1.96–4.46, p <0.001) and respiratory symptoms (OR = 3.14, CI 1.95–5.14, p<0.001) were associated with increased likelihood of epinephrine administration, in contrast to integumentary symptoms (OR = 0.98, CI 0.54–1.81, p = 0.961) and gastrointestinal symptoms (OR = 0.62, CI 0.39–1.00, p = 0.053). CONCLUSIONS: Less than half of the patients with moderate and severe anaphylaxis received epinephrine according to guidelines. In particular, gastrointestinal symptoms seem to be misrecognised as serious symptoms of anaphylaxis. Training of the emergency medical services and emergency department medical staff and further awareness are crucial to increase the administration rate of epinephrine in anaphylaxis.